THE USE OF RICE POLISHING MACHINE TOSHI KINHE MPGV 50 IN INCREASING RICE YIELD IN RMU AT SUBAK BENGKEL, TABANAN - Pande Made Ari Ananta Paramarta; Ni Ketut Karyati (International Conference on Multidisciplinary Research Perspective, 2025)
Rice (Oryza sativa L.) is a major commodity that determines national food security, with rice yield as an important indicator of post-harvest success. Rice yield in Subak Bengkel, Tabanan is still low (45–50%) due to the use of conventional Rice Milling Units (RMUs) that are less efficient. This study aims to analyze the adoption of the Toshi Kinhe MPGV 50 Rice Polishing Machine innovation and its effect on increasing rice yield. The research method uses SEM-PLS to analyze innovation adoption factors and multiple linear regression to examine the effect of technology on yield. The results show that innovation adoption is significantly influenced by relative advantage (0.42), observability (0.40), compatibility (0.36), and trialability (0.31), while complexity (-0.28) has a negative effect. The regression model with R² = 0.71 shows that machine adoption, usage intensity, grain moisture content, operator experience, and RMU capacity explain 71% of the variation in rice yield. The Toshi Kinhe MPGV 50 machine has been proven to increase yield by more than 5% and improve the physical quality of rice. Consequently, machine adoption needs to be supported by operator training, grain moisture management, and field demonstration programs to expand its application and improve farmer welfare.